2016
DOI: 10.1242/bio.019638
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of theDrosophilaNinein-related centrosomal protein Bsg25D causes mitotic defects and impairs embryonic development

Abstract: The centrosome-associated proteins Ninein (Nin) and Ninein-like protein (Nlp) play significant roles in microtubule stability, nucleation and anchoring at the centrosome in mammalian cells. Here, we investigate Blastoderm specific gene 25D (Bsg25D), which encodes the only Drosophila protein that is closely related to Nin and Nlp. In early embryos, we find that Bsg25D mRNA and Bsg25D protein are closely associated with centrosomes and astral microtubules. We show that sequences within the coding region and 3′UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 77 publications
4
39
0
Order By: Relevance
“…We examined the distribution of Bsg25D / ninein ( nin ) mRNA with smFISH. Nin is a pericentrosomal protein ( Kowanda et al, 2016 ; Zheng et al, 2016 ) and nin mRNA localizes near centrosomes in syncytial embryos ( Lécuyer et al, 2007 ). In NC 11 and NC 12 embryos, nin mRNA appeared evenly dispersed within the cytosol, similar to gapdh ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the distribution of Bsg25D / ninein ( nin ) mRNA with smFISH. Nin is a pericentrosomal protein ( Kowanda et al, 2016 ; Zheng et al, 2016 ) and nin mRNA localizes near centrosomes in syncytial embryos ( Lécuyer et al, 2007 ). In NC 11 and NC 12 embryos, nin mRNA appeared evenly dispersed within the cytosol, similar to gapdh ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The γ-TuRC-tethering protein NEDD1 is one potential candidate involved in microtubule anchoring at centrosomes as it can tether minus ends to ectopic locations . Another protein frequently implicated in minus-end anchoring at both centrosomes and non-centrosomal sites is ninein (Goldspink et al, 2017;Kowanda et al, 2016;Mogensen et al, 2000;Wang et al, 2015); however, it is unclear whether ninein can recognize γ-TuRCbound or -free microtubule minus ends.…”
Section: Microtubule Minus-end Anchoring To Subcellular Structuresmentioning
confidence: 99%
“…While Nin's molecular mechanisms of action are not well understood, the conserved N-terminal domain of Drosophila Nin can associate directly with MTs (Kowanda et al, 2016). Nin localizes to Drosophila muscle and wing ncMTOCs (Zheng et al, 2016) and to the apparent ncMTOC in oocytes (Kowanda et al, 2016). We found that Nin localized to the fat body perinuclear ncMTOC ( Figure 19A).…”
Section: Patronin Cooperates With Ninein To Organize the Fat Body Ncmmentioning
confidence: 64%
“…Nin is a MT minus-end protein with anchoring function at the centriole subdistal appendages in mammals (Mogensen et al, 2000;Delgehyr et al, 2005), but Nin also has ncMTOC roles in mammals, Drosophila and C. elegans (Mogensen et al, 2000;Wang et al, 2015b;Zheng et al, 2016;Goldspink et al, 2017). While Nin's molecular mechanisms of action are not well understood, the conserved N-terminal domain of Drosophila Nin can associate directly with MTs (Kowanda et al, 2016). Nin localizes to Drosophila muscle and wing ncMTOCs (Zheng et al, 2016) and to the apparent ncMTOC in oocytes (Kowanda et al, 2016).…”
Section: Patronin Cooperates With Ninein To Organize the Fat Body Ncmmentioning
confidence: 99%
See 1 more Smart Citation